2012
DOI: 10.1007/s13593-012-0103-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced blackberry production using Pseudomonas fluorescens as elicitor

Abstract: et al.. Enhanced blackberry production using Pseudomonas fluorescens as elicitor. Agronomy for Sustainable Development, Springer Verlag/EDP Sciences/INRA, 2013, 33 (2), pp.Abstract This report shows for the first time the ability of Pseudomonas fluorescens N21.4 to trigger the secondary metabolism of blackberries, Rubus fruticosus, in the field. Blackberries are an excellent source of bioactive compounds as compared to other marketable berries. Biotic elicitation with plant growth-promoting rhizobacteria has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 26 publications
3
27
0
Order By: Relevance
“…Blackberry fruits are an important source of bioactive compounds, among which are flavonols, catechins, and anthocyanins (Garcia-Seco et al, 2013). These molecules have been reported to have beneficial effects to prevent metabolic syndrome at different levels such as cardiovascular disease and type II diabetes; hence, including blackberry on human diet is beneficial for health (Tavares et al, 2013; Feresin et al, 2016; Sarkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Blackberry fruits are an important source of bioactive compounds, among which are flavonols, catechins, and anthocyanins (Garcia-Seco et al, 2013). These molecules have been reported to have beneficial effects to prevent metabolic syndrome at different levels such as cardiovascular disease and type II diabetes; hence, including blackberry on human diet is beneficial for health (Tavares et al, 2013; Feresin et al, 2016; Sarkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It releases siderophores and chitinases, triggering defensive metabolisms in Solanum lycopersicum , Arabidopsis thaliana , and Glycine max . It also increases isoflavone content in G. max and fruit yield in blackberries …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies in field conditions have shown that two bacterial strains, Bacillus amyloliquefaciens and Pseudomonas fluorescens , are able to trigger secondary metabolisms in different plants . The aim of this study was therefore twofold: (i) to evaluate the ability of these two strains to modulate the bioactive levels in strawberry and raspberry produced in counter season, and (ii) to demonstrate the positive effects of these extracts on blood glucose regulation, hypertension, and inflammatory processes, comparing winter and spring samples, indicative of adverse and favorable conditions, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the control of plant diseases using classical pesticides raises serious concerns about food safety, environmental effects and pesticide resistance, sustainable agricultural practices must involve the use of environmentally friendly alternatives for effective plant disease control. In addition to balanced fertilization (Abro et al, 2013;Dordas, 2008), soil biosolarization (Domínguez et al, 2014), and other agroecological practices (Wezel et al, 2014), biocontrol microbes (BMs) have increasingly been used to suppress phytopathogens for sustainable agriculture (Camprubí et al, 2007;García-Seco et al, 2013;Khaled et al, 2008;Ongena and Jacques, 2008;Weller, 2007). Although the inoculation of plants with BMs is now well established, the formulation of inocula with reliable and consistent effects under field conditions remains a bottleneck that limits industrial-scale applications of BMs.…”
Section: Introductionmentioning
confidence: 99%